Fusion of protoplasts with irradiated microprotoplasts as a tool for radiation hybrid panel in citrus - Bona, Claudine Maria de; Stelly, David; Junior, J. Creighton Miller; Louzada, Eliezer Silva (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to combine asymmetric somatic hybridization (donor-recipient fusion or gamma fusion) to microprotoplast-mediated chromosome transfer, as a tool to be used for chromosome mapping in Citrus. Swinglea glutinosa microprotoplasts were irradiated either with 50, 70, 100 or 200 gamma rays and fused to cv. Ruby Red grapefruit or Murcott tangor protoplasts. Cell colonies were successfully formed and AFLP analyses confirmed presence of S. glutinosa in both 'Murcott' tangor and 'Ruby Red' grapefruit genomes.
Keywords: Citrus; Swinglea glutinosa; asymmetric somatic hybridization; gamma rays; hybrid cell lines; radiation hybrid mapping